Analyzing Healthpreneur Determinants for Low-Socioeconomic Ethnic Families - Jayanagara, Oscar; Patricia, Anastasia (Aptisi Transactions On Technopreneurship (ATT), 2025)
Access to health services is a critical factor in improving the well-being of low-socioeconomic status families. However, many families in Surakarta face challenges in utilizing healthcare services. The purpose of this study is to explore the relationship between educational level, family economic status, and other demographic factors with their willingness to access health services at RSUD Dr. Moewardi, Surakarta. The purpose of this study is to determine how education, economic status, and demographics influence healthcare-seeking behavior among low-socioeconomic families, with the goal of improving healthcare accessibility and understanding barriers to usage. A quantitative approach was employed, using a Confirmatory Factor Analysis (CFA) model. Data were collected through a structured questionnaire distributed to 116 respondents from low-socioeconomic families in Surakarta, with a focus on education, income, and healthcare-seeking behavior. The data were analyzed using SPSS to identify relationships between variables. The analysis showed significant differences in healthcare access behavior based on educational level, with families possessing higher education levels being more likely to utilize healthcare services. Economic factors were also identified as a strong predictor of healthcare access willingness. The study highlights the importance of addressing educational and economic barriers to improve access to health services for low-socioeconomic families. Policymakers must consider these factors when developing healthcare programs aimed at increasing participation from marginalized groups.